2010
DOI: 10.1016/j.micres.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantification of periodontitis-related bacteria using a novel modification of Invader PLUS technologies

Abstract: The Invader PLUS technology is a sensitive, rapid method for the detection and quantification of nucleic acid. While the original technology is based on the amplification by polymerase chain reaction (PCR) of the target sequence followed by its detection using the Invader technology, the current modification allows simultaneous PCR amplification and Invader reaction. The PCR primers and the Invader probes are designed to operate at the same temperature. This allows simpler design and faster results. This techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 13 publications
1
42
0
1
Order By: Relevance
“…on August 28, 2018 by guest http://jcm.asm.org/ sitivity was the greatest of the three methods (HP, TaqMan, and Invader), as reported previously (20). Genotyping error for rs8099917 by direct sequencing due to novel SNP.…”
Section: Vol 49 2011 Best Predictor For Treatment Of Chronic Hepatisupporting
confidence: 68%
“…on August 28, 2018 by guest http://jcm.asm.org/ sitivity was the greatest of the three methods (HP, TaqMan, and Invader), as reported previously (20). Genotyping error for rs8099917 by direct sequencing due to novel SNP.…”
Section: Vol 49 2011 Best Predictor For Treatment Of Chronic Hepatisupporting
confidence: 68%
“…Tadokoro et al showed that the Invader Plus method could quantify periodontal pathogens with good correlation with the results of real-time PCR (19). In this assay, DNA sequences were amplified and quantified using the Invader technology.…”
Section: Discussionmentioning
confidence: 99%
“…15 Bacterial DNA was purified using MagNA Pure LC (Roche, Basel, Switzerland) and added to a 15-ll reaction mixture containing 50 lM d-NTP, 700 nM primer probe, 70 nM Invader oligo, and 2.5 U AmpliTaq Stoffel fragment (Applied Biosystems, Foster City, CA, USA), and the Cleavase XI Invader core re-agent kit (Genomic DNA, Third Wave Technologies Inc., Madison, WI, USA) consisting of Cleavase XI FRET mix and Cleavase XI enzyme ⁄ MgCl 2 solution. The reaction mixture was preheated at 95°C for 2 minutes, followed by 35 cycles of two-step PCR (95°C for 1 minute, 63°C for 1 minute) using LightCycler 480 (Roche, Basel, Switzerland).…”
Section: Quantitative Analysis By Pcr-invader Assaymentioning
confidence: 99%